Synthesis of Kinematic Schemes for Surface Machining on Metal-Cutting Machines (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This study presents a systematic approach to the synthesis of kinematic schemes for surface machining on metal-cutting machines. The research focuses on optimizing the geometric and kinematic parameters that determine machining efficiency, precision, and surface quality. Through an in-depth analysis of generating elements and surface formation models, the paper explores methods such as copying, envelopment, trace, and contact for constructing generating lines. A classification of complete and partial surface formation is provided, along with a discussion on the implications of these models for machine tool design. The results highlight the importance of rational tool path design and motion coordination to improve form-generation accuracy and tool performance. The study concludes by proposing combined formation methods to leverage the strengths of elementary approaches in practical applications.